Chemical, rheological properties and microstructure of road asphalt prepared from deoiled asphalt, slurry oil and polymers. (10th October 2020) - Xin, Xue; Jiang, Hongguang; Liang, Ming; Yao, Zhanyong; Zhang, Jizhe; Luo, Weixin; Zhang, Xiaomeng
Highlights: The modification of slurry oil for de-oiled asphalt leads to a more reasonable chemical composition. Radial SBS is efficient on improving high temperature performance of asphalt blends. The performance of blends with 10% CR is comparable to that containing 5% SBS. Microstructure and micromorphology of blends verified their mechanical response. Abstract: The demand for high quality asphalt binder is continuously increasing in road construction and paving industry, most of which derives from vacuum distillation of petroleum. Meanwhile, deoiled asphalt (DOA) and slurry oil are the by-products of solvent deasphalting and fluid catalytic cracking (FCC) respectively. This paper developed high-quality road asphalt binder from DOA modified with FCC slurry oil and polymers. Different styrene-butadienestyrene (SBS) and crumb rubber (CR) were selected as polymer modifiers. The optimized blending ratio of DOA/slurry was determined. Moreover, the effects of various modifiers on rheological properties, low-temperature cracking resistance, and microstructure of the resulting asphalt were evaluated. The results indicated that the incorporation of FCC slurry oil results in a more reasonable chemical composition and the improved cracking resistance of the blends. For different structure of SBS, radial SBS is more efficient to enhance the high temperature performance of DOA/slurry blends. The DOA/slurry with 10% CR shows the approximate value in viscosity, complex modulus and |G*|/sinδ in comparison of sample with 5% linear SBS, demonstrating significant effectiveness of CR on improving the high temperature performance of DOA/slurry. Linear SBS is a better candidate improving low temperature performance of DOA/slurry. The FTIR analysis indicated that the double bonds of SBS take part in the chemical cross-linking reaction, whereas CR improves property of asphalt only by physical interactions. Regarding to morphology, linear SBS presents the homogeneous dispersion in the form of cycle particles, whereas radial SBS displays a rather irregular form of polymer phase. CR phase shows elongated features and forms a continuous phase when reaching 20% content, which significantly reinforces the mechanical property of the asphalt.